‘Just give up the ball’: In search of a third space in relationships between male youth workers and young men involved in violence - Harris, Pete (Criminology & criminal justice, 2022)
This article critically examines the employment of male youth workers in the field of youth crime prevention. It focuses on how their relationships with young men involved in violence might (or might not) support young men and promote desistance. It does this via the presentation of a single psychosocial case study that examines the relationship between a Black male youth worker and a young Black man who becomes involved in violence and then falls victim to violence to other young men in his neighbourhood. It illuminates how some male workers’ resources of masculine and street capital may be advantageous in terms of reaching some young men, but may also create barriers to reaching others. The study focuses on how both men in the case struggle to ‘give up the ball’ – a metaphor the article adopts for the act of conceding masculine capital in the street field. I suggest that for the relationship to provide the support this young man needed, it required the creation of a third space between him and his youth worker, that is, a vantage point from where they could both examine their masculinity and how this was related to their respective psychic vulnerabilities. I argue that the two men’s investments in different discourses of masculinity were more significant (in terms of the desistance-promoting potential of their relationship) than the similarity in their racial or class backgrounds. The case highlights the need for a more nuanced understanding of youth work relationships and for provision of adequate support and supervision for all male workers that incorporates thorough consideration of their personal and professional identity formation, especially the most heavily gendered aspects.